The prevailing leadership styles of public school principals and their relation to the quality of education from the point of view of quality education evaluators in Jordan - Haddad, Maha Saleh Ibrahim (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the prevailing leadership styles (democratic,autocratic, and sedentary) among the principals of public schools and their relation to the quality of education from the point of view of the evaluators of the quality of education in Jordan. In order to achieve the objectives of the study, the researcher prepared a questionnaire consisting of (35) items dealing with two fields. The first field consisted of (15) items distributed to the prevailing leadership styles among the principals. The study sample consisted of (100) residents of the quality of education in the Ministry of Education. The study found that the three leadership styles of public school principals were in favor of the democratic leadership model with an average of 3.68 and a high degree of appreciation followed by an autocratic pattern with an average of 3.35 and a medium degree of appreciation. The mean pattern was average (2.60) with a medium degree of appreciation. The average level of assessment of the quality indicators of education and accountability was also found. The total arithmetic average of the axis (3.35). It also showed an average level of assessment of the indicators of the quality of education and accountability, where the total arithmetic average of the axis (3.35). The study found that the three leadership styles of public school principals were in favor of the democratic leadership pattern at an average of 3.68 and high, followed by the autocratic pattern with an average of 3.35 and a medium grade. The plurality came last with an average of (2.60) Education (adequacy, security, credibility, effectiveness), and a statistically significant relationship between prevailing leadership styles and the quality of education in Jordan. Based on the results, the study recommended activating and directing school principals to follow the democratic pattern in the practice of leadership and moving away from the autocratic and sedimentary patterns. he results also showed a strong positive correlation between leadership patterns of school principals and quality indicators of education. Based on the results, the study recommended activating and directing school principals to follow the democratic pattern in the practice of leadership and moving away from the autocratic and sedimentary patterns.